2014
DOI: 10.1039/c3em00597f
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the complete and partial photooxidation of black carbon in surface waters

Abstract: Increasing wildfire activity in the Alaskan Arctic may result in new sources of black carbon (BC) to arctic watersheds. Black carbon, primarily comprised of condensed aromatics, is one of the most chemically recalcitrant fractions of organic carbon. However, lateral transfer of particulate and dissolved BC from soils to sunlit surface waters is increasingly suggested to result in the photochemical mineralization of BC to CO₂. While sunlight can also partially photooxidize aromatic compounds in surface waters, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
111
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(120 citation statements)
references
References 56 publications
(110 reference statements)
8
111
1
Order By: Relevance
“…47 These condensed aromatics, which can account for more than half of the DOM structure in the extract, impart the DOM with lower H/C and O/C ratios and a much higher double bond equivalent. 47,48 The ash extracts possessed lower reactivity in forming THM and HAA suggesting that the condensed aromatics were likely less reactive THM and HAA precursors. Although high specific THM and HAA FP often positively link to high DOM aromaticity (or high SUVA 254 ), 49 SUVA 254 could not explain the DOM reactivity in THM or HAA formation across the three DOM sources in this study (r 2 = 0.06, P = 0.12−0.19; Figure S3, Supporting Information).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…47 These condensed aromatics, which can account for more than half of the DOM structure in the extract, impart the DOM with lower H/C and O/C ratios and a much higher double bond equivalent. 47,48 The ash extracts possessed lower reactivity in forming THM and HAA suggesting that the condensed aromatics were likely less reactive THM and HAA precursors. Although high specific THM and HAA FP often positively link to high DOM aromaticity (or high SUVA 254 ), 49 SUVA 254 could not explain the DOM reactivity in THM or HAA formation across the three DOM sources in this study (r 2 = 0.06, P = 0.12−0.19; Figure S3, Supporting Information).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This method does not target aliphatic or other non-condensed compounds in pyDOM, as they likely do not form BPCA compounds upon nitric acid oxidation. Aliphatic and O-containing components are likely to be more soluble than the condensed aromatic fraction, thus may represent a large portion of pyDOM, as directly identified using FTICR-MS (Podgorski et al, 2012;Ward et al, 2014). It is also unclear if the BPCA method quantifies pyC, exclusively.…”
Section: Pyrogenic Carbon Quantification Methodsmentioning
confidence: 99%
“…However, since an increase in both CDOM concentration and DBC concentration was observed for LMW fractions after photodegradation (Table 5.1), it is suggested that smaller aromatic photo-products were indeed generated from the decomposition of CDOM and DBC in HMW fractions for this particular DOM sample. Although the present study is corroborated by previous observations where DBC is preferentially removed through photo-reactive processes vs. bulk DOC Ward et al, 2014), it was also discovered that DBC is associated with HMW fractions is more photo-labile than DBC in LMW fractions ( Fig. 5.2).…”
Section: Resultssupporting
confidence: 81%